2016
DOI: 10.1186/s12889-016-3224-5
|View full text |Cite
|
Sign up to set email alerts
|

Parental knowledge, attitudes and beliefs regarding fever in children: an interview study

Abstract: BackgroundFever is one of the most common childhood symptoms. It causes significant worry and concern for parents. Every year there are numerous cases of over- and under-dosing with antipyretics. Caregivers seek reassurance from a variety of sources including healthcare practitioners. The aim of this study was to describe parental knowledge, attitudes and beliefs regarding management of childhood fever in children aged 5 years and under.MethodSemi-structured interviews were conducted with 23 parents at six ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 53 publications
2
70
0
5
Order By: Relevance
“…7 There is a need for educating the parents about the physiological nature of fever, antipyretic dosing, home remedial measures and to withhold the use of antibiotics in early fever episodes as also expressed with concern in other studies. 18,19 There is a need to provide information via counselling, media campaigns, so as to effectively reduce the parental anxiety regarding fever, desire to antibiotic use where it may not be justified. 20,21 The role of media in playing a pivotal role in achieving these goals cannot be emphasized more.…”
Section: Resultsmentioning
confidence: 99%
“…7 There is a need for educating the parents about the physiological nature of fever, antipyretic dosing, home remedial measures and to withhold the use of antibiotics in early fever episodes as also expressed with concern in other studies. 18,19 There is a need to provide information via counselling, media campaigns, so as to effectively reduce the parental anxiety regarding fever, desire to antibiotic use where it may not be justified. 20,21 The role of media in playing a pivotal role in achieving these goals cannot be emphasized more.…”
Section: Resultsmentioning
confidence: 99%
“…As one of the most accessible healthcare providers with convenient locations, long opening hours, no appointment necessary and free consultation, pharmacists are an ideal option for offering guidance. Previous research has shown that parents value pharmacists as providers of medical information [52]. Published research has demonstrated that non-pharmacist staff also have a large role to play when providing consultations for non-prescription medications, however pharmacists tended to perform better than non-pharmacist staff in these consultations [53].…”
Section: Discussionmentioning
confidence: 98%
“…6 As a result, parents get worried when their children experience an episode of fever. 7 Caretakers' apprehension about fever arises from concerns over the cause of fever, risk of hospitalization, and occurrence of potential harmful effects of fever in their children. 8 Brain damage, febrile convulsions, and death are among the frequently reported harmful effects of fever in children.…”
Section: Introductionmentioning
confidence: 99%